Capitalism and Suffering - Olivier, Bert (PINS-Psychology in Society, 2015)
The present article is an exploration of the relationship between neoliberal capitalism and suffering in a broad sense, which includes everything from economic and physical suffering, psychic suffering in the form of anxiety, self-doubt, uncertainty and stress, to more acute suffering, such as identifiable pathologies. Its point of departure is the patho-analytic principle, that one can gain an understanding of the general psychic condition of humanity by focusing on the characteristic traits of a pathology such as, for example, obsessional neurosis, and examining the possibility that some of these characteristics are encountered in the population at large. Focusing first on evidence of severe economic suffering under the impact of what Klein calls “disaster capitalism”, the argument proceeds to Parker’s claim, that the typical subject under capitalism displays the character of obsessional neurosis, then to Salecl’s examination of capitalism’s “ideology of choice”, Verhaeghe’s investigation of the effects of a market-based economy on psychic health, and Federici’s claim that there are signs of increasing resistance to capitalist labour. It concludes with some prospective thoughts on Salecl’s, and Hardt and Negri’s diagnosis of present social conditions under capitalism.